The effect of ampule size of fentanyl on perioperative intravenous opioid dosing - David M Rosenfeld; Kathleen E Knapp; Joshua A Spiro; Andrew W Gorlin; Harish Ramakrishna; Terrence L Trentman (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: There are limited data on the effect of ampule size on drug dosing. The objective of this study is to determine the effect of ampule size on perioperative opioid dosing and post-anesthesia care unit (PACU) outcomes. Material and Methods: This was a retrospective review of patients undergoing robotically assisted laparoscopic radical prostatectomy before and after a 5-ml fentanyl ampule was discontinued. The primary outcome was intraoperative opioid administration divided into fentanyl at induction of anesthesia, total fentanyl, and total opioid. Secondary outcomes observed in PACU included the opioid administered, visual analog scale (VAS) pain scores, postoperative nausea and vomiting, and length of stay in PACU. Results: A total of 100 patients (50 PRE and 50 POST) were included. In the intraoperative opioid administration, mean (SD) of fentanyl at induction was 117.0 (49.3) in PRE group and 85.0 (35.4) μg in POST group (P < 0.01). The total fentanyl requirement was 247.0 (31.0) in PRE group and 158.5 (85.1) μg in POST group (P < 0.01). The total opioid in intravenous morphine equivalents (IVME) was 34.1 (5.8) in PRE group and 23.2 (6.8) mg in POST group (P < 0.01). Among the secondary outcomes, mean (SD) of IVME of opioid was 7.7 (8.2) in PRE group and 9.9 (8.1) mg in POST group (P = 0.18). The VAS pain score on arrival was 0.7 (1.4) in PRE group and 3.8 (3.3) in POST group (P < 0.01). The cumulative VAS pain score was 2.3 (2.0) in PRE group and 3.3 (2.2) in POST group (P < 0.01). The length of stay was significantly more in POST group, 193.8 (75.8) minutes, as compared with PRE group, 138.6 (61.0) minutes (P < 0.01). Conclusions: A change in the ampule size significantly affected intraoperative dosing, PACU pain scores, and PACU length of stay in patients undergoing robotically assisted laparoscopic radical prostatectomy under general anesthesia. This was explained by clinician's desire to conserve the drug and avoid the complex process of narcotic waste disposal.